The colonial and the porfiriato urbanization: inheritance of urban (un)sustainability in Mexico City - R. Isela Jasso-Flores; Lorena Escobar-Chanona; Rogelio O. Corona-Núñez (ESTOA: Revista de la Facultad de Arquitectura y Urbanismo de la Universidad de Cuenca)
Mexico City has experienced different periods of urban transformation, especially during the Colonial era and the Porfiriato. These periods have left a mark on urban (un)sustainability not only in Mexico City but also in other colonial cities. Using cartographic time series and the functional concept of neighborhoods, this study analyzes their influence on urban sustainability in the 21st century. We evaluate this sustainability through the environmental indicator of forest biomass. Our results suggest that colonial neighborhoods show a central concentration of forest biomass, decreasing as they move away from the colonial square (Zócalo). In contrast, during the Porfiriato, biomass is concentrated in the urbanization near the Zócalo, distributed in median strips and gardens. This study lays the groundwork for understanding the legacy of urban (un)sustainability throughout the periods of urbanization in Mexico.